Source geometry factors for HDR 192Ir brachytherapy secondary standard well-type ionization chamber calibrations. (21st March 2015) - Shipley, D R; Sander, T; Nutbrown, R F
Abstract Well-type ionization chambers are used for measuring the source strength of radioactive brachytherapy sources before clinical use. Initially, the well chambers are calibrated against a suitable national standard. For high dose rate (HDR) 192Ir, this calibration is usually a two-step process. Firstly, the calibration source is traceably calibrated against an air kerma primary standard in terms of either reference air kerma rate or air kerma strength. The calibrated 192Ir source is then used to calibrate the secondary standard well-type ionization chamber. Calibration laboratories are usually only equipped with one type of HDR 192Ir source. If the clinical source type is different from that used for the calibration of the well chamber at the standards laboratory, a source geometry factor, ksg, is required to correct the calibration coefficient for any change of the well chamber response due to geometric differences between the sources. In this work we present source geometry factors for six different HDR 192Ir brachytherapy sources which have been determined using Monte Carlo techniques for a specific ionization chamber, the Standard Imaging HDR 1000 Plus well chamber with a type 70010 HDR iridium source holder. The calculated correction factors were normalized to the old and new type of calibration source used at the National Physical Laboratory. With the old Nucletron microSelectron-v1 (classic) HDR 192Ir calibration source, ksg was found to be in the range 0.983 to 0.999 and with the new Isodose Control HDR 192Ir Flexisource ksg was found to be in the range 0.987 to 1.004 with a relative uncertainty of 0.4% (k = 2). Source geometry factors for different combinations of calibration sources, clinical sources, well chambers and associated source holders, can be calculated with the formalism discussed in this paper.